2023
DOI: 10.1038/s41392-023-01546-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial heterogeneity in diseases

Long Chen,
Mengnan Zhou,
Hao Li
et al.

Abstract: As key organelles involved in cellular metabolism, mitochondria frequently undergo adaptive changes in morphology, components and functions in response to various environmental stresses and cellular demands. Previous studies of mitochondria research have gradually evolved, from focusing on morphological change analysis to systematic multiomics, thereby revealing the mitochondrial variation between cells or within the mitochondrial population within a single cell. The phenomenon of mitochondrial variation featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 473 publications
0
8
0
Order By: Relevance
“…However, as we have shown, these cells can be a promising and convenient model for studying the relationship between MN morphology and pathology associated with neurodegeneration. Furthermore, recent articles have shown that the MN can be a target for regulation of stem cell differentiation and for relieving various pathological conditions [50,51]. This is of great interest in light of the fact that neurons can be obtained from the fibroblasts of patients with PD to replace dead cells in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, as we have shown, these cells can be a promising and convenient model for studying the relationship between MN morphology and pathology associated with neurodegeneration. Furthermore, recent articles have shown that the MN can be a target for regulation of stem cell differentiation and for relieving various pathological conditions [50,51]. This is of great interest in light of the fact that neurons can be obtained from the fibroblasts of patients with PD to replace dead cells in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has also demonstrated that cell lineage-specific mitochondrial gene expression emerges early in development which contributes to the tissue specificity 20 . And our group also reviewed the mitochondria heterogeneity between different cells 58 . And mitochondria have been increasingly recognized as the important information process system beyond the traditional role of powerhouse 29 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The cancer cells rely only on glycolysis to meet their bioenergetic demands, but they still are dependent on some of the mitochondrial electron transport (mETC) byproducts for effective cell proliferation. This suggests that respiratory defects or dysfunction in mitochondrial dynamics could be the primary cause of cancer, as observed by Otto Warburg in the ‘Warburg effect ( Cantor and Sabatini, 2012 ; Ward and Thompson, 2012 ; Chen et al, 2023 ; Kaur et al, 2023 ; Wang and Patti, 2023 ). These discoveries emphasize the impact of mitochondrial function in cancer progression and could have significant implications for cancer treatment.…”
Section: Introductionmentioning
confidence: 97%
“…These discoveries emphasize the impact of mitochondrial function in cancer progression and could have significant implications for cancer treatment. Additionally, mitochondria are linked to redox regulation, cell signaling, apoptosis, and cell function and fate ( DeBerardinis and Chandel, 2016 ; Chen et al, 2023 ). Furthermore, various studies revealed that mitochondrial metabolic reprogramming is related to the development of genitourinary cancer such as bladder cancer, prostate cancer, and kidney cancer.…”
Section: Introductionmentioning
confidence: 99%